COMPARTILHAMENTO DE SERVIÇOS NA ADMINISTRAÇÃO PÚBLICA FEDERAL: ANÁLISE DOS FATORES DE APLICABILIDADE NA AUTARQUIA FEDERAL - Oliveira, Edilson Rios de (2013)
This study examines, among the factors that can facilitate or discourage the implementation of a model of the Shared Services Center (CSC) in federal agency CNEN / RJ, which would be more relevant and more weight in view of the area managers sharing proposal . As research questions was analyzed if the CSC model can be applied as a tool for organizational restructuring in the public area. Bibliometric survey was conducted on the subjects managerial public administration, organizational change and motivators of CSC. A questionnaire was adapted from a model tested on the subject, and applied together with area managers share object; finance, human resource, procurement and information technology. The data were processed through the standard scale liket and analyzed. The results indicate that the factors that favor the implementation of a model of the CSC CNEN / RJ are the most significant factors that disfavor the use of the model. Research indicates that, based on examples from other countries, the CSC model can contribute as a tool for organizational restructuring in response to drivers of change identified in the company, in order to react acertivamente.